Capillary zone electrophoresis for fatty acids with chemometrics for the determination of milk adulteration by whey addition. (15th December 2016) - de Oliveira Mendes, Thiago; Porto, Brenda Lee Simas; Bell, Maria José Valenzuela; Perrone, Ítalo Tuler; de Oliveira, Marcone Augusto Leal
Highlights: Alternative method for determination of milk adulteration by whey. Quality control tests in the field of dairy industry. Fast, simple and ecofriendly separation method. Abstract: Adulteration of milk with whey is difficult to detect because these two have similar physical and chemical characteristics. The traditional methodologies to monitor this fraud are based on the analysis of caseinomacropeptide. The present study proposes a new approach to detect and quantify this fraud using the fatty acid profiles of milk and whey. Fatty acids C14:0, C16:0, C18:0, C18:1, C18:2 and C18:3 were selected by gas chromatography associated with discriminant analysis to differentiate milk and whey, as they are present in quite different amounts. These six fatty acids were quantified within a short time by capillary zone electrophoresis in a set of adulterated milk samples. The correlation coefficient between the true values of whey addition and the experimental values obtained by this technique was 0.973. The technique is thus useful for the evaluation of milk adulteration with whey, contributing to the quality control of milk in the dairy industry.